ALPPS in neuroendocrine liver metastases not amenable for conventional resection – lessons learned from an interim analysis of the International ALPPS Registry. Issue 4 (April 2020) - Linecker, Michael; Kambakamba, Patryk; Raptis, Dimitri A.; Malagó, Massimo; Ratti, Francesca; Aldrighetti, Luca; Robles-Campos, Ricardo; Lehwald-Tywuschik, Nadja; Knoefel, Wolfram T.; Balci, Deniz; Ardiles, Victoria; De Santibañes, Eduardo; et al.
Abstract: Background: Surgery is the most effective treatment option for neuroendocrine liver metastases (NELM). This study investigated the role of associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) as a novel strategy in treatment of NELM. Methods: The International ALPPS Registry was reviewed to study patients who underwent ALPPS for NELM. Results: From 2010 to 2017, 954 ALPPS procedures from 135 international centers were recorded in the International ALPPS Registry. Of them, 24 (2.5%) were performed for NELM. Twenty-one patients entered the final analysis. Overall grade ≥3b morbidity was 9% after stage 1 and 27% after stage 2. Ninety-day mortality was 5%. R0 resection was achieved in 19 cases (90%) at stage 2. Median follow-up was 28 (19–48) months. Median disease free survival (DFS) was 17.3 (95% CI: 7.1–27.4) months, 1-year and 2-year DFS was 73.2% and 41.8%, respectively. Median overall survival (OS) was not reached. One-year and 2-year OS was 95.2% and 95.2%, respectively. Conclusions: ALPPS appears to be a suitable strategy for inclusion in the multimodal armamentarium of well-selected patients with neuroendocrine liver metastases. In light of the morbidity in this initial series and a high rate of disease-recurrence, the procedure should be taken with caution.